2010
DOI: 10.1016/j.seppur.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

THMs precursor removal by an integrated process of ozonation and biological granular activated carbon for typical Northern China water

Abstract: a b s t r a c tThe removal of trihalomethanes (THMs) precursor and natural organic matter (NOM) by an integrated process of ozonation and biological granular activated carbon filtration (BGAC) as a deep water treatment process was investigated in pilot-scale tests. A comparison is also made with granular activated carbon filtration (GAC). The characteristics of the THMs precursor and the THMs formation potential (THMFP) were investigated by resin adsorption and ultrafiltration. The results show that the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…In the effluent of the PAC and PAC-SBR systems, the fluorescence peak C disappeared after the treatment. This result suggested that these organic compounds were easily adsorbed by PAC, which was also illustrated in previous researches [28,29]. Therefore, PAC helped to remove the compounds that were difficult for micro-organisms to biodegrade.…”
Section: Fluorescence Analysis Of Wastewater In Different Treatment Ssupporting
confidence: 77%
“…In the effluent of the PAC and PAC-SBR systems, the fluorescence peak C disappeared after the treatment. This result suggested that these organic compounds were easily adsorbed by PAC, which was also illustrated in previous researches [28,29]. Therefore, PAC helped to remove the compounds that were difficult for micro-organisms to biodegrade.…”
Section: Fluorescence Analysis Of Wastewater In Different Treatment Ssupporting
confidence: 77%
“…The colorization, unpleasant odors and unpleasant tastes in 1 Chlorine for Water Disinfection: Properties, Applications and Health Effects water can be attributed to NOM. The NOM is also responsible to bacterial regrowth through the network distribution systems (Yan et al 2010). Over the years, various technologies and processes have been investigated for reducing the NOM during water treatment.…”
Section: Control and Elimination Of Disinfection By-productsmentioning
confidence: 99%
“…The NOM can be partially removed using a conventional treatment (coagulation, flocculation, sedimentation and filtration) or by using granular activated carbon (GAC) (Sadiq and Rodriguez 2004;Hanigan et al 2012). Another effective method to control DBPs in drinking water is the use of alternative disinfection processes such as ozonation (Yan et al 2010), photocatalysis (Murray and Parsons 2006), photo-electro-catalysis (Selcuk and Bekbolet 2008), direct photolysis (UV) (Hansen et al 2013) and electrochemical disinfection (Matilainen and Sillanpää 2010) among others. Besides, a better control of operational factors (e.g.…”
Section: Control and Elimination Of Disinfection By-productsmentioning
confidence: 99%
“…Recently, some researches carried on bench-scale or pilotscale O 3 -BAC experiments and proved an effective removal of TOC (total organic carbon), UV254 (ultraviolet absorbance under 254 nm), turbidity, ammonia, and DBPs precursors by the O 3 -BAC system (Chu et al 2012;Guo et al 2013;Yan et al 2010). Studies on wastewater treatment or water reclamation plants also found O 3 -BAC effective in removing organic chemicals and reducing biological activity and toxity of water (Qian et al 2013;Reungoat et al 2010;Reungoat et al 2012).…”
Section: Introductionmentioning
confidence: 99%